On Problem of Professional Training of Social Workers within the Framework of Higher Education - L. Z. Karavanova; R. I. Kachayev; M. G. Sergeyeva; I. S. Samokhin; N. L. Sokolova (Научный диалог)
The issue of training of social workers in higher education is considered. The relevance of the research is caused by changes of socio-economic and technological nature, taking place in modern society, implying the training of specialists of higher level: “multi-functional,” meeting international standards of training professionals to implement certain urgent tasks. Professionalization refers to the process of improving a person’s knowledge, skills and abilities in the context of an activity that involves the presence of a certain subject represented in the culture of a given society, and ways of working with it. The authors rely on the indicators of the level of professional training offered by Yu. P. Povarenkov: professional effectiveness, professional identity and professional maturity. The novelty of the research lies in destinguishing three levels of “co-existence essence” of professional training of social professionals: adaptive-orientational, subject-effective and innovative-creative. The authors dwell on the position, according to which the student evolves as a subject of activity only in certain educational conditions: motivating environment of the educational institution as a factor contributing to the active development of new knowledge, skills and abilities; well-organized training and education aimed at increasing the effectiveness of students and teachers; tracking the dynamics of creative development of students, their improvement in personal and professional relationships.